Innovation in Virtual Environments as a University Teacher's Approach (Docentes 2.0 Journal, 2024)
In recent years, the world population has experienced various natural events that caused significant changes in the educational field; educational centers have had to adapt to distance learning in all subjects quickly. The purpose of this research article was to analyze research related to virtual teaching techniques in the university context. For this purpose, a study was carried out using a qualitative approach, interpretive paradigm, and documentary design. It used a systematic review as a methodology, relying on the PRISMA statement to select them. Twenty-six articles constituted the documents examined. The results revealed that teachers used various techniques to innovate in online classes, such as project-based learning, problem-based learning, cooperative learning, and competency-based learning, in addition to the flipped classroom. Specifically, the approach to flipped classrooms was the most studied, with more articles on it. In conclusion, the studies indicated that, in virtual education, university teachers used different techniques to improve student learning. However, more research is required to optimize pedagogical practices to improve student achievement.
Keywords: Learning; education; innovation; techniques; virtual